The Dopaminergic System in the Aging Brain of Drosophila - White, Katherine E.; Humphrey, Dickon M.; Hirth, Frank (Frontiers in Neuroscience, 2010)
Drosophila models of Parkinson’s disease are characterised by two principal phenotypes: the specific loss of dopaminergic neurons in the aging brain and defects in motor behavior. However, an age-related analysis of these baseline parameters in wildtype Drosophila is lacking. Here we analysed the dopaminergic system and motor behavior in aging Drosophila. Dopaminergic neurons in the adult brain can be grouped into bilateral symmetric clusters, each comprising a stereotypical number of cells. Analysis of TH>mCD8::GFP and cell type-specific MARCM clones revealed that dopaminergic neurons show cluster-specific, stereotypical projection patterns with terminal arborization in target regions that represent distinct functional areas of the adult brain. Target areas include the mushroom bodies, involved in memory formation and motivation, and the central complex, involved in the control of motor behavior, indicating that similar to the mammalian brain, dopaminergic neurons in the fly brain are involved in the regulation of specific behaviors. Behavioral analysis revealed that Drosophila show an age-related decline in startle-induced locomotion and negative geotaxis. Motion tracking however, revealed that walking activity and exploration behavior, but not centrophobism increase at late stages of life. Analysis of TH>Dcr2, mCD8::GFP revealed a specific effect of Dcr2 expression on walking activity but not on exploratory or centrophobic behavior, indicating that the siRNA pathway may modulate distinct dopaminergic behaviors in Drosophila. Moreover, dopaminergic neurons were maintained between early- and late life, as quantified by TH>mCD8::GFP and anti-TH labelling, indicating that adult onset, age-related degeneration of dopaminergic neurons does not occur in the aging brain of Drosophila. Taken together, our data establish baseline parameters in Drosophila for the study of Parkinson’s disease as well as other disorders affecting dopaminergic neurons and movement control.